Baiq Nuril’s Amnesty Impacts on Legal Certainty in Indonesia - aditya risky haryo; Asyri Febriana; Muhammad Rif'an; Tria Vista Maghfira (Faculty of Law, University of Mataram, 2020)
Purpose of this work is to provide another view to the reader on baiq nuril’s amnesty impact on legal certainty. Type of this research is normative legal research. After analyzing legal materials, it can be concluded that, first of all, baiq nuril’s amnesty could be categorized as amnesty which base on individual principle, which it has a precedent as regulated in Presidential Decree Number 449 of 1961, secondly, several positive impacts of President Joko Widodo’s amnesty to baiq nuril is providing legal protection to women and motivating government to clarify regulation on amnesty as soon as possible.